Mtbf Analysis Of The Two-Unit Series System With Repair Facility (International Journal of Engineering and Computer Science, 2017)
This paper discusses mean time between failure and availability analysis in a two-unit series repairable system with three states under consideration. First two states are taken as up states and the third state is down state. A single repair facility is available which repairs the units on first-come-first-serve basis. Taking failure rates as identically distributed exponential random variable and repair rate as exponential, Mean time between failure and Steady State Availability are calculated. Denoting the failure times of the components as λ and repair time as μ expression for steady state availability and MTBF have been derived using semi-markov process and regenerative point technique. The difference equations are developed and solved using Laplace transform.